The impact of velocity on pull and recovery times and average pull forces in freestyle swimming - Soultanakis, H.; Platanou, T. (Biomechanics and Medicine in Swimming X, 2006)
Twelve non competitive swimmers participated in this study. The purpose of the study was to evaluate the impact of two different velocities on arm pull and recovery times, as well as to evaluate the average force applied. Force sensors, were positioned between the swimmers' fingers and were connected through cables to a Computer. Participants swam two 25-meter length trials, a slow swim trial (SS) and a. fast swim trial (FS), with a rest of 2 minutes in between swims. As velocity increased, stoke rate increased, stroke length decreased, and reductions in swimming (20%), arm pull (15.4 %) and arm recovery (45.7%) times (seconds) were recorded. A significant increase (62.3%) in average pull force (N) was recorded in the fast swim trial. As far as arm contribution to swimming speed is concerned it appears that pull and recovery times as well as forces exerted by the arms directly affect velocity.